Adab Memuliakan Guru Perspektif KH. Ahmad Muthohar Bin Abdurrahman dalam Kitab Al-Akhlaq Al-Mardliyah Wa Al-Adab Al-Syar’iyyah - Najih, Muchammad; Irfan, Agus (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2022)
This study aims to deternine the etiquette of glorifying teachers from the perspective of KH. Ahmad Muthohar bin Abdurrahman in the Book of Al-Akhlaq Al-Mardhiyah wa Al-Adab Al-Syar'iyyah. This type of research is library research (library research), with data collection through literature (library method). This research was conducted using a qualitative data analysis approach and using content analysis techniques. Based on the results of the study, adab glorifies teachers from the perspective of KH. Ahmad Muthohar bin Abdurrahman there are many, the researcher explains only three, namely students seeking knowledge are intended only for Allah, students are likened to sick people (patients) needing doctors to recover, and upholding etiquette when students confide in teachers. The concept of adab glorifying teachers has been outlined by KH. Ahmad Muthohar bin Abdurrahman in the book Al-Akhlaq Al-Mardhiyah wa Al-Adab Al-Syar'iyyah can be applied in formal and non-formal school institutions.